Lay causes of binge drinking in the United Kingdom and Australia: a causal network diagram approach - Keatley, David A.; Ferguson, Eamonn; Lonsdale, Adam; Hagger, Martin S. (Oxford University Press, 2017)
Binge drinking is associated with deleterious health, social and economic outcomes. This study explored the lay understanding of the causes of binge drinking in members of the general public in the United Kingdom and Australia. Participants in the United Kingdom (N = 133) and Australia (N = 102) completed a network diagram exercise requiring them to draw causal paths and provide path strength ratings between 12 candidate factors (24-h opening, age, alcohol advertizing, alcohol availability, boredom, drinking culture, income, low cost, parental influence, peer pressure, stress and supermarket discounts) and binge drinking. Results indicated good consistency in paths across samples, although differences in frequency and strength ratings for some paths were found. Drinking culture, peer pressure and low alcohol cost were perceived as direct causes of binge drinking in both samples. Low alcohol cost and drinking culture were most frequently viewed as direct causes of binge drinking in UK and Australian participants, respectively. Supermarket discounts and low cost of alcohol were most frequently viewed as indirect causes of binge drinking by UK and Australian samples. Findings reflect general awareness and prominence of factors affecting binge drinking in both national groups. Findings may inform the development of campaigns to promote public support policies to curb binge drinking.